Dust storms attenuation measurements at 14GHz and 21GHz in Sudan - Elfatih A., A. Elsheikh; Islam, Md. Rafiqul; Ismail, Ahmad Fadzil; Habaebi, Mohamed Hadi; Chebil, Jalel (Institute of Electrical and Electronics Engineers Inc., 2016)
A study on dust storm effect on Microwave links in arid area covering a wide range of radiofrequency was running for one year in Khartoum, Sudan. The study involves computerized monitoring of Transmitted and Received signal levels of two Microwave links operating at (14GHz) and (21GHz) as well as an automatic weather station. This paper presents a description of the experiment and reports results of measuring dust storms as they affect the radio wave propagation specially frequencies above 10GHz. The effect of dust storms on propagation is studied by measuring the storm parameters; visibility and induced attenuation due to these storms. The results have been compared with the attenuation prediction models. It has been shown that the measured attenuation caused by the dust storms at 0.01% availability is about eight and elven times the calculated attenuation using Zain and Chu models at 14.5GHz respectively. Whereas, the measured attenuation due to dust storms at 21.2GHz and 0.01% availability is about ten and fourteen times the calculated attenuation using Zain and Chu models respectively.